Domestic violence, ethnic diversity, and political and economic change in an upland community of Vietnam - Kwiatkowski, Lynn (Alterstice)

(untitled) (Alterstice, 2013)
Domestic violence occurs among a variety of ethnic groups in Vietnam, within diverse social, cultural, and environmental contexts. This article explores the role that culture is perceived to play in influencing manifestations of domestic violence among different ethnic groups living in the same community in Vietnam, in relation to the social structural influences on this form of gender violence. It examines the perceptions of wife abuse among members of three ethnic groups—the Kinh, Muong, and Dao—living in an upland community in a province in northern Vietnam. In this article, first, domestic violence is situated among the ethnic groups, who live within a changing social, political, and economic environment, through an exploration of the reasons members of the ethnic groups offered for husbands' abuse of their wives. Second, problems abused women continue to face, despite the implementation of a new domestic violence law, and new orientations among professionals and community leaders toward provision of services for abused women are assessed.